The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s40616-017-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Derived Equivalence Relations of Basic Geography Skills in Children with Autism

Abstract: The present study evaluated the efficacy of a stimulus-equivalence training procedure in teaching basic geography skills to two children with autism. The procedures were taken directly from a standardized training curriculum based in stimulus equivalence theory called Promoting the Emergence of Advanced Knowledge Equivalence Module (PEAK-E). Results suggest that the procedures were efficacious in directly training several geographical relations, as well as promoting the derivation of several untrained relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…The results from the current study suggest that EBI can be used to teach advanced educational topics of history, mathematics, and chemistry to this population. This provides the first demonstration of EBI to teach these topics to individuals with adolescents with autism, and also serves as a systematic replication of Dixon et al (2016) and Dixon et al (2017) by further demonstrating that EBI procedures are effective and efficient teaching techniques worthy of continued investigation.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…The results from the current study suggest that EBI can be used to teach advanced educational topics of history, mathematics, and chemistry to this population. This provides the first demonstration of EBI to teach these topics to individuals with adolescents with autism, and also serves as a systematic replication of Dixon et al (2016) and Dixon et al (2017) by further demonstrating that EBI procedures are effective and efficient teaching techniques worthy of continued investigation.…”
Section: Discussionmentioning
confidence: 75%
“…The purpose of the current study was to evaluate the efficacy of EBI in teaching academic relations germane to history, chemistry and mathematics to adolescents with autism. Previous research in this area has demonstrated the effectiveness of EBI in teaching academically relevant topics, such as geometry (Dixon et al, ) and geography (Dixon et al, ). In the current study, all participants demonstrated mastery of the targeted skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uma vez que o MTS permite o estabelecimento de um número maior de relações além daquelas diretamente treinadas, sua ampla utilização em pesquisas básicas (e.g., Sidman, 1994;Sidman, 2009) e aplicadas (e.g., McLay, Sutherland, Church, & Tyler-Merrick, 2013; Rehfeldt, 2011)ocorredevido a economia no tempo de ensino que pode ser benéfica para umavariedade de populações.Com participantes com autismo, tal procedimento já foi empregado em pesquisas básicas (e.g., Eikeseth & Smith, 1992;Groskreutz, Karsina, Miguel, & Groskreutz, 2010; O'Connor, Barnes-Holmes, & Barnes-Holmes, 2011) e aplicadaspara ensinoo ensino de habilidades diversas comogeografia (Dixon et al, 2017;LeBlanc, Miguel, Cummings, Goldsmith, & Carr, 2003), habilidades com dinheiro (Keintz, Miguel, Kao, & Finn, 2012), habilidades acadêmicas (Stanley, Belisle, & Dixon, 2018), música (Arntzen, Halstadtro, Bjerke, & Halstadtro, 2010a;Hill, Griffith, & Miguel, 2019), seguir cronogramas de atividades (Miguel, Yang, Finn, & Ahearn, 2009) e relações entre letras maiúsculas/minúsculas (Varella & De Souza, 2015) e números/quantidades(e.g., McLay, Church, & Sutherland, 2014).Entretanto, esses estudos mostram que apenas algumas das relações testadas emergem (e.g., Arntzen et al, 2010), que emergência de todas as relações ocorre somente para alguns dos participantes (e.g., Groskreutz et al, 2010;Keintz et al, 2012;McLay et al, 2014)ou após o uso de treinos remediativos, como otreino de tato dos estímulos após a falha nos testes (e.g., Eikeseth & Smith, 1992) e treino com múltiplos exemplares (e.g., O'Connor et al, 2011).Além disso, entre os estudos publicados com essa população alguns apresentam problemas metodológicos como, o uso de participantes que já formavam classes de equivalência de acordo avaliações prévias (e.g., Dixon et al, 2017;Stanley et al, 2018), treino não intencional das relações emergentes (e.g., LeBlanc et al, 2003) e participantes que obtiveram porcentagem altas porcentagens de acerto nos pré-testes de relações emergentes (e.g., Miguel et al, 2009;…”
Section: Sumáriounclassified